Key issues for the next farm bill: is a farm program buyout possible? - Orden, David (2005)
This presentation explores a policy option that the United States might utilize to reduce the long-run fiscal cost of subsidies and facilitate agricultural trade liberalization, while providing substantial transition support to farmers. The focus is on whether reforms that decouple support programs, which are designed to reduce potential production- and trade distorting effects, can be made more convincing through a long-term buyout that would end farm subsidies. Buyouts have not been feasible in the past but recent reforms for peanuts and tobacco provide evidence of what might be done and the conditions under which it occurs. Although the political-economy circumstances may not be conducive yet, estimates are provided of the potential cost of a buyout of the main decoupled U.S. subsidies of fixed direct and counter-cyclical payments. A program buyout of this type should be on the agenda in discussion of the next farm bill.